Estimation and application of population attributable fraction in ecological studies - Cheng-Kuan Lin; Szu-Ta Chen (BMC, 2019)
Abstract Estimation of population attributable fraction (PAF) requires unbiased relative risk (RR) by using either Levin's or Miettinen's formula, on which decision depends on the available exposure information in reference group, not the types of studies. For ecological studies and studies with aggregated outcomes, once having unbiased RRs, Levin's and Miettinen's formulae would provide identical PAF estimates. PAF could also be applied to compare relative burdens of disease between countries across time, which is an additional information in consideration of country-level policies.